Implementasi Penyembunyian Data pada Metadata PNG Menggunakan Enkripsi Fernet (AES) Berbasis Password dengan Python - Ulvia Rahmi; Mutia Hafizah Quranul; Putri Dian; Rahmtul Amna (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid exchange of digital information necessitates robust security measures to protect sensitive data from unauthorized access. This research proposes a hybrid security model combining cryptography and steganography to hide information within PNG image metadata. The system utilizes Fernet symmetric encryption, which is built on top of AES-128, to secure the message before embedding it into the metadata fields. A password-based key derivation ensures that only authorized users can decrypt the content. By leveraging Python for implementation, the study demonstrates that metadata-based steganography provides a secure alternative to traditional pixel-based methods, as it does not alter the visual quality of the image. The results indicate that the encrypted metadata is resilient to basic image viewing while maintaining data integrity.